PEMANFAATAN KOMBINASI EKSTRAK BUAH NANAS DAN PEPAYA UNTUK MENINGKATKAN KUALITAS DAGING ITIK PETELUR AFKIR - Aju Tjatur Nugroho Krisnaningsih; Dyah Lestari Yulianti (Universitas Tribhuwana Tunggadewi, 2015)
One alternative to meet the needs of the market and the increasing availability of public interest will be the consumption of meat, it can be done by utilizing the potential of laying duck meat rejected. This study aims to determine the quality of the meat rejected by the use of a combination of pineapple and papaya extracts. The method used is an experimental study using a completely randomized design (CRD). Soaking duck meat with the addition of a combination of salvage pineapple and papaya fruit extract that consists of 4 levels: 0% Pineapple: 0% Papaya, Pineapple 25%: 75% Papaya, Pineapple 50%: 50% and 75% Pineapple Papaya: Papaya 25%. Data were analyzed using Variant Analysis and continued with Duncan's multiple range test if there is a difference. The results showed a significant difference to the levels of protein, fat and meat tenderness (P0.05) rejects laying duck meat